Analisis Peran Orang Tua Terhadap Perilaku Seksual Pranikah Remaja Di Kecamatan Tabukan Utara Tahun 2025 - Tooy, Gracia Christy; Hinonaung, Jelita Siska Herlina; Umboh, Melanthon Junaedi; Rambi, Christien Angreni; Kasaluhe, Meityn Disye; Tatangidatu, Maryati Agustina (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Premarital sexual behavior among adolescents is often influenced by encouraging factors, such as internal intentions, social support from parents and friends, ease of access to information related to pornography and opportunities that encourage premarital sexual behavior among adolescents. This study aims to analyze the relationship between parental roles and premarital sexual behavior among adolescents in North Tabukan District, Sangihe Islands Regency. This research employed an analytical survey design with a cross-sectional approach. The study population consisted of parents and adolescents, with a total sample of 120 respondents selected through consecutive sampling based on inclusion and exclusion criteria. Data were collected using questionnaires on parental roles and premarital sexual behavior, and analyzed using the Chi-Square test. The results showed that most parents had good roles (71.7%), while the majority of adolescents exhibited good premarital sexual behavior (99.2%). Although the statistical test indicated no significant relationship between parental roles and premarital sexual behavior (p = 0.110), descriptive analysis revealed a tendency for better parental roles to be associated with more positive adolescent behavior. Furthermore, attitudes showed a significant relationship with premarital sexual behavior (p = 0.000). In conclusion, parental roles, knowledge, and attitudes play a crucial role in shaping healthy premarital sexual behavior among adolescents; therefore, family-based interventions should be strengthened through open communication and comprehensive sexual education.